The Reality Of Service In The Field Of Children With Mental Retardation at Awat Institute in the Erbil City - Awring Ismail jalal; Omar Ibrahim Azeez (Zanco Journal of Humanity Sciences)
The main aim of this research is to demonstrate the realiaty of social and educational services of children with mental retardation from the point of view of social workers and teachers at Awat Institute in Erbil governorate.This research is a descriptive research where Qualitative method is used as a main method in addition to utilizing Thematic analysis to analyes the data collected in the reaseach. The research population is Awat institute which is specialized in the education of children with mental retardation. Moreover, the research samples consist of 23 teachers and 4 social workers at Awat institute where they intentionally selected. Data collection process conducted through semi structured interview and observation method. The most significant result obtained from this research is the condition of social and educational services from the perspective of teachers and social workers are not at the acceptable level. The most important recommendation made in this research and presetnted to MOLSA is the recruitment of sepecialists in various areas (psychologist, education specialists, physiotherapist, Language and Speech Training Specialists) for Awat institute. Furthermore, the most important recommendation made for future researche is to conduct a Comparative research between government and non-government institutes with regard to provision of the level of services for children with mental retardation.